Trauma and Recovery on War's Border : A Guide for Global Health Workers - Maung, Cynthia, Dr; Murakami, Nancy; Allden, Kathleen (Book collections on Project MUSE., 2015)
A guide for mental health workers in regions traumatized by war, human rights violations, and poverty across the globe.